2022
DOI: 10.1084/jem.20211191
|View full text |Cite
|
Sign up to set email alerts
|

CD127 imprints functional heterogeneity to diversify monocyte responses in inflammatory diseases

Abstract: Inflammatory monocytes are key mediators of acute and chronic inflammation; yet, their functional diversity remains obscure. Single-cell transcriptome analyses of human inflammatory monocytes from COVID-19 and rheumatoid arthritis patients revealed a subset of cells positive for CD127, an IL-7 receptor subunit, and such positivity rendered otherwise inert monocytes responsive to IL-7. Active IL-7 signaling engaged epigenetically coupled, STAT5-coordinated transcriptional programs to restrain inflammatory gene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…Moreover, despite the fact that the literature reports a reduction of non-classical monocytes in COVID-19 patients ( 68 ), in our dataset the only subpopulation altered in frequency was the one of cMo cytotoxic monocytes, which increased in severe and moderate patients. Finally, our data showing the expression of IL-7R in cytotoxic monocytes are consistent with the presence of IL7R + monocytes/macrophages in COVID-19 BALF ( 69 ), and further support the hypothesis that these cells are key players in the progress of the disease.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, despite the fact that the literature reports a reduction of non-classical monocytes in COVID-19 patients ( 68 ), in our dataset the only subpopulation altered in frequency was the one of cMo cytotoxic monocytes, which increased in severe and moderate patients. Finally, our data showing the expression of IL-7R in cytotoxic monocytes are consistent with the presence of IL7R + monocytes/macrophages in COVID-19 BALF ( 69 ), and further support the hypothesis that these cells are key players in the progress of the disease.…”
Section: Discussionsupporting
confidence: 85%
“…Monocytes belong to the monocyte-phagocytic system ( 33 ). Monocytes are the first line of host defense, which are a key mediator of acute and chronic inflammation ( 34 ), and can induce immune-inflammatory responses ( 35 ). HDL-c has anti-inflammatory properties and may be essential for the prevention of other inflammatory diseases ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NKG2D receptor was also a new potential target to regulate the direct interaction between SARS-CoV-2 and NK cells and could be used as a therapeutic target for COVID-19 ( 11 ). Single-cell transcriptome analyzes of human inflammatory monocytes from COVID-19 and RA patients showed that a group of CD127 (IL-7 receptor subunit) positive cells induced initially inactive monocytes to respond to IL-7 and negatively affected the inflammatory phenotype of monocytes ( 67 ).…”
Section: Discussionmentioning
confidence: 99%